TNF-α Regulated Endometrial Stroma Secretome Promotes Trophoblast Invasion - You, Yuan; Stelzl, Patrick; Joseph, Dana N.; Aldo, Paulomi B.; Maxwell, Anthony J.; Dekel, Nava; Liao, Aihua; Whirledge, Shannon; Mor, Gil (Frontiers in Immunology, 2021)
Successful implantation requires the coordinated migration and invasion of trophoblast cells from out of the blastocyst and into the endometrium. This process relies on signals produced by cells in the maternal endometrium. However, the relative contribution of stroma cells remains unclear. The study of human implantation has major technical limitations, therefore the need of in vitro models to elucidate the molecular mechanisms. Using a recently described 3D in vitro models we evaluated the interaction between trophoblasts and human endometrial stroma cells (hESC), we assessed the process of trophoblast migration and invasion in the presence of stroma derived factors. We demonstrate that hESC promotes trophoblast invasion through the generation of an inflammatory environment modulated by TNF-α. We also show the role of stromal derived IL-17 as a promoter of trophoblast migration through the induction of essential genes that confer invasive capacity to cells of the trophectoderm. In conclusion, we describe the characterization of a cellular inflammatory network that may be important for blastocyst implantation. Our findings provide a new insight into the complexity of the implantation process and reveal the importance of inflammation for embryo implantation.